Work Stress And Job Satisfaction Case Of Adult Learners In Malaysia. - Asaari, Muhammad Hasmi Abu Hassan; Karia, Noorliza (2005)
Work is regarded as important criteria in determining the individual's career achievement. Academic excellence of an individual will be used to suit the person's ability to secure a good job.